2020
DOI: 10.3892/ol.2020.11353
|View full text |Cite
|
Sign up to set email alerts
|

ZW10 interacting kinetochore protein may serve as a prognostic biomarker for human breast cancer: An integrated bioinformatics analysis

Abstract: ZW10 interacting kinetochore protein (ZWINT) is an essential component for the mitotic spindle checkpoint and has been reported to be upregulated in numerous types of human cancer. Nonetheless, its role in breast cancer (BC) remains unclear. Herein, it was demonstrated that the expression of ZWINT was significantly higher in BC than in normal breast tissues, on the basis of integrated analysis of bioinformatics studies, cancer database analyses and immunohistochemical detection. Elevated ZWINT levels were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…In order to understand the expression pathways of these key genes, these key genes were defined as a set of genes for GSEA, which is a computational tool commonly employed to interpret gene expression data by evaluating whether a pre-defined set of genes demonstrates statistically significant ( Subramanian et al, 2005 ; Li et al, 2020 ). The terms with P -value < 0.05 obtained in GSEA was considered significant and the top 10 terms were visualized using “ggplot2” package.…”
Section: Methodsmentioning
confidence: 99%
“…In order to understand the expression pathways of these key genes, these key genes were defined as a set of genes for GSEA, which is a computational tool commonly employed to interpret gene expression data by evaluating whether a pre-defined set of genes demonstrates statistically significant ( Subramanian et al, 2005 ; Li et al, 2020 ). The terms with P -value < 0.05 obtained in GSEA was considered significant and the top 10 terms were visualized using “ggplot2” package.…”
Section: Methodsmentioning
confidence: 99%
“…TRIM17 is also involved in mitosis by inducing the degradation of key components of the mitotic spindle machinery, midbodies and the kinetochore protein ZWINT, via autophagy and UPS, respectively [ 68 , 73 ]. Notably, ZWINT is upregulated in many human cancers and is associated with poor clinical prognosis and early recurrence [ 145 , 146 ]. Conversely, ZWINT knockdown effectively inhibits proliferation of glioblastoma cells in vitro and suppresses glioblastoma growth in vivo [ 146 ].…”
Section: Trim17 and Diseasesmentioning
confidence: 99%
“…For instance, Zwint expression was indicated to be associated with the expression levels of PCNA, Cdc25C, cyclin B1 and CDK1( 11 ). Li et al ( 10 ) reported that high Zwint expression was closely associated with cell cycle-related molecules and pathways, such as Myc targets V1/2, DNA repair, mitotic spindle, G2M checkpoint and E2F targets. In addition, Peng et al ( 13 ) demonstrated that Zwint knockdown affected the expression of molecules associated with TNF signaling and other pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be hypothesized that an abnormal expression or structure of Zwint may be associated with carcinogenesis. Previous studies have reported that Zwint is overexpressed in various types of tumors and is associated with a poor prognosis ( 10-12 ). In addition, it has been demonstrated that Zwint may act as an oncogene ( 11 , 13 ).…”
Section: Introductionmentioning
confidence: 99%